Customer satisfaction through services offer by Metro Driving Academy (MDA) towards its customer / Wan Nur Hidayah Abdul Nasir - Abdul Nasir, Wan Nur Hidayah (2009)
The purpose of the study is to measure the customer satisfaction among Metro Driving Academy (MDA) through service offered. Customer satisfaction defines how to recognize when a customer is satisfied, and how to enhance satisfaction. In order to get the data, researcher had conducted a survey. From the finding, researcher receives a positive response from the respondents. This due from the reliability of the scale is above 0.6. Overall, respondents are very satisfied with the service offers in term of the course and training provided, facilities and equipment and thumb print system.